Validity of a wearable sensor for stroke detection in youth tennis players - Cui, Y.; Zhou, Y.; Jozef, B.; Shen, Y. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: The practice of athlete monitoring in tennis used to be done via notational analysis, so that coaches or analysts manually count the stroke and empirically estimate the load player may experience. The advancement of in micro-sensors and intelligent algorithms allow for the automatic and more tennis-specific quantification of the load, which enables the monitoring of multiple players in real-time. The aim of the study was to validate a commercially available trunk-mounted wearable sensor in detecting the strokes of different techniques in youth tennis player.